Media Cotory untuk Meningkatkan Literasi, Minat, dan Keterampilan Siswa dalam Menulis Cerita Komik Bergambar - Agus Suyanto (Jurnal Didaktika Pendidikan Dasar, 2023)
Writing skills are one of the language skills that are difficult for students to master. This is caused by several factors, namely low literacy, lack of vocabulary mastery and students’ interest in learning activities, and the absence of learning media used by the teacher. To overcome these problems, especially in learning to write narrative text, the author applies the use of Comic Photo Story (Cotory) media. This media is used to improve literacy, students’ interest and writing skills of characters comics in class IX students of SMPN 1 Bancar. This research was carried out in Classroom Action Research which consisted of four stages, namely: planning, acting, observing, and reflecting. The assessment instrument used is the result of the assessment of students’ comics, observations and questionnaires. This research was carried out by the author in several meetings. The result of student observations and questionnaires showed that students’ literacy and interest increased significantly. Meanwhile, the scores obtained by students from the results of the comics they made showed that the students’ writing skills of character comics also increased significantly where 100% of students achieved the predetermined KKM score.